Determinants of Export Performance in ASEAN Region : Panel Data Analysis - Oo, Thida; Kueh, Jerome Swee Hui; Daw, Tin Hla (Canadian Center of Science and Education, 2019)
International trade is one of the major aspects that grow tremendously in Southeast Asia and export is regarded as main accelerators of growth in either developed or developing countries. The objective of this study is to determine the determinants of export performance for ASEAN countries. In this study, panel Autoregressive Distributed Lag (ARDL) method is adopted for time period between 2000 to 2015. Empirical findings indicate that there is a long-run relationship between determinants of export such as interest rate, economic growth and foreign direct investment with export performance of ASEAN countries. Therefore, policy makers need to strategize their policies to move towards closer cooperation among the ASEAN countries, especially promoting sustainable exportation in the region.